A escrita da cidade partida: identidade e alteridade em Capão Pecado - Luciana Paiva Coronel (Estudos de Literatura Brasileira Contemporânea)
This article discusses the representation of the city in the novel Capão Pecado, by Ferréz. It deviates from the strong tendency of considering all cities alike in the Brazilian fiction scenery by means of a narrative that takes place in a geographical area within the outskirts of São Paulo. This area is characterized by violence and extreme poverty and it works as the headquarters of a movement of self-assurance of the have-nots. The novel brings a broken and raw text, written with the cooperation of cultural leaders of the area. There is a mix of fictional aspects and a great deal of testimony. The author seeks to build a community feeling among the people who live in Capão Redondo and at the same time he opposes the downtown area of the city, where the people who benefit from the inequities of the status quo live.